An RP-HPLC Method for the Concurrent Measurement of Almitrine and Raubasine in Tablet and Bulk Forms: Development and Validation - Vijayalakshmi, Rajendran; Ansari, Shaik Sadhik; Reddy, Satti Sandeep; Sandya, Pilli (International Journal of Pharmaceutical Investigation, 2025)
Background This study work introduces a straightforward, sensitive, specific, and efficient stability-indicating HPLC approach designed for the simultaneous measurement of Almitrine and Raubasine in both pre-formulation and drug formulation contexts. Materials and Methods The suggested RP-HPLC method was established using a Zorbax Eclipse XDB-C18 column (250x4.6 mm, 5 µm) at ambient temperature, employing an isocratic mobile phase of orthophosphoric acid (0.1%) in water and acetonitrile (40:60) at a flow rate of 1 mL/min. Results The eluted analytes were detected at a wavelength of 248 nm. In accordance with ICH recommendations, the validity and stability of the medications under various environmental circumstances were assessed. The established method exhibited linearity within the concentration ranges of 1-12 μg/mL for Almitrine and 3-36 μg/mL for Raubasine respectively. The retention times for Raubasine and Almitrine were determined to be 2.839 and 2.089 respectively. The accuracy achieved by the proposed approach ranged from 99.01 to 100.7. The Relative Standard Deviation (RSD) for the precision research results was determined to be less than 1%. Conclusion The established RP-HPLC method exhibited exceptional precision, specificity, sensitivity, and stability indication. The proposed analytical approach offered a sensitive and specific test for the measurement of Almitrine and Raubasine. Consequently, the method can be employed in the quality control department for routine examination of Almitrine and Raubasine estimate.
Keywords: Almitrine; Isocratic elution; Raubasine; RP-HPLC; Simultaneous